Comparative evaluation of granulometric distribution in grains processed by ball and hammer Mills. - Bonilla Bermeo, Stefanie; Noblecilla Arévalo, Fernando; Torres Tapia, Iván; Valdiviezo Rogel, Carlos (Ingeniería Química y Desarrollo, 2026)
The grinding of grains is fundamental in industrial processes, where the resulting particle size distribution directly impacts product quality. This study aimed to compare the granulometric distribution of corn and soybeans processed using a hammer mill, ball mill, and their combination. Samples of corn and soybeans were ground using three configurations: hammer mill, ball mill, and sequential milling with both. The resulting material was sieved to determine weight retained per mesh and calculate characteristic diameters (D10, D50, D90). Additional particle microscopy and ANOVA were performed to evaluate significant differences. The hammer mill produced coarse, heterogeneous distributions, especially for soybeans (D50 ≈ 2.9 mm). The ball mill generated a higher proportion of fine particles in corn (D50 ≈ 1.38 mm) but was ineffective for soybeans (D50 ≈ 3.53 mm). The mill combination achieved the most uniform distribution for both grains (D50 ≈ 1.05–1.25 mm). ANOVA detected no global significant differences, though morphological and distributional disparities were observed in sieve analysis. The combined milling approach optimized granulometric distribution, overcoming the limitations of each individual equipment.